2022
DOI: 10.1136/gutjnl-2022-328185
|View full text |Cite
|
Sign up to set email alerts
|

Human gut microbiota after bariatric surgery alters intestinal morphology and glucose absorption in mice independently of obesity

Abstract: ObjectiveBariatric surgery is an effective treatment for type 2 diabetes (T2D) that changes gut microbial composition. We determined whether the gut microbiota in humans after restrictive or malabsorptive bariatric surgery was sufficient to lower blood glucose.DesignWomen with obesity and T2D had biliopancreatic diversion with duodenal switch (BPD-DS) or laparoscopic sleeve gastrectomy (LSG). Faecal samples from the same patient before and after each surgery were used to colonise rodents, and determinants of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Interestingly, only peak glucose levels during the OGTT were lower in RYGB recipient mice, suggesting that the RYGB-associated gut microbiota may contribute specifically to lowering glucose absorption. This is in line with findings from a recent study suggesting that the gut microbiota after metabolic surgery improves oral glucose tolerance by lowering jejunal absorptive capacity rather than by enhancing insulin action ( 14 ). Notably, the recipient GF mice in that study also had lower fecal abundance of Erysipelotrichaceae family members ( 14 ), suggesting a role for this member of the gut microbiota in promoting host glucose absorption.…”
Section: Observationsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, only peak glucose levels during the OGTT were lower in RYGB recipient mice, suggesting that the RYGB-associated gut microbiota may contribute specifically to lowering glucose absorption. This is in line with findings from a recent study suggesting that the gut microbiota after metabolic surgery improves oral glucose tolerance by lowering jejunal absorptive capacity rather than by enhancing insulin action ( 14 ). Notably, the recipient GF mice in that study also had lower fecal abundance of Erysipelotrichaceae family members ( 14 ), suggesting a role for this member of the gut microbiota in promoting host glucose absorption.…”
Section: Observationsupporting
confidence: 92%
“…For example, the weight loss and improvements in glycemic control normally found in RYGB-treated and VSG-treated rats or mice, respectively, with diet-induced obesity is attenuated by prior depletion of the gut microbiota with antibiotic treatments ( 8 , 9 ). Additionally, transfer of the cecal/fecal microbiota from metabolic surgery-treated mice ( 10 ), rats ( 11 , 12 ) or humans ( 13 , 14 ) to germfree (GF) mice can lead to weight loss and protection from fat gain ( 10 , 13 ) or to improvements in glycemic control in recipients ( 11 , 12 , 14 ). These studies, however, do not disentangle the potential influences that the gut microbiota, body weight, and glycemia have on each other.…”
Section: Observationmentioning
confidence: 99%
“…Canagliflozin, a SGLT2 inhibitor with also a modest inhibitory effect on SGLT1, was found to tendentially increase Bacteroidetes and decrease Firmicutes abundance, and to increase cecal SCFAs content in mice ( 111 ). Selective inhibition of SGLT1 has demonstrated to restore gut dysbiosis in renal failure mice ( 112 , 113 ).…”
Section: Effect Of Current Nafld/mafld Treatment Options On the Gut M...mentioning
confidence: 99%
“…Another similar study in 2021 transferred colonic microbiota from rats six weeks after RYGB surgery into germ-free mice and reported that body weights were similar between recipient groups [19]. A well-described recent study in 2022 transplanted the faecal microbiota from human patients before and after two different types of gastric weight loss surgery into mice with differences in particular bacterial genera between different groups of recipient mice [20]. In this study, the microbiota was transferred into both germ-free and conventional laboratory mice and there were no differences in weight gain or in fat mass between any of the groups.…”
Section: Microbiota Transplantation Following Gastric Bypass Surgerymentioning
confidence: 99%